2007
DOI: 10.1111/j.1600-079x.2007.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial properties of melatonin in an experimental model of pancreatic cancer

Abstract: Pancreatic cancer is a major health problem because of the aggressiveness of the disease and the lack of effective systemic therapies. Melatonin has antioxidant activity and prevents experimental genotoxicity. However, the effect of melatonin in pancreatic cancer has not been tested. Pancreatic carcinogenesis was induced by N-nitrosobis (2-oxopropyl)amine (BOP) in Syrian hamsters. Melatonin was administered during the BOP-induction phase (12 wk) and/or following the postinduction phase (12 wk). Different param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The involvement of oxidative stress has been demonstrated in several experimental models of pancreatic cancer [35,36,37,38,39]. The present study showed that the administration of anti-antiangiogenic (celecoxib) and chemotherapeutic (capecitabine) drugs in monotherapy and combined administration recovered the antioxidant status and reduced the progression of pancreatic adenocarcinomas in an experimental model of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The involvement of oxidative stress has been demonstrated in several experimental models of pancreatic cancer [35,36,37,38,39]. The present study showed that the administration of anti-antiangiogenic (celecoxib) and chemotherapeutic (capecitabine) drugs in monotherapy and combined administration recovered the antioxidant status and reduced the progression of pancreatic adenocarcinomas in an experimental model of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 48%
“…The induction of pancreatic cancer by BOP has histopathological and biochemical similarities with human pancreatic adenocarinoma [35,36,37,38,40,41,42]. Antioxidant drugs such as octreotide [36], tamoxifen [40], vitamin A, C and E [35] and melatonin [38] have been shown to have antitumoral properties in BOP-induced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent paper reported that melatonin was efficacious in a Syrian hamster model of pancreatic cancer, where N-nitroso-bis(2-oxopropyl)amine was the inducing agent. The evidence suggested that melatonin's anti-oxidative properties were responsible for the observed effect [50]. Prosure (Abbott) is a proprietary nutritional supplement that is often prescribed to cancer patients in order to assist them in gaining weight and improving their quality of life [51].…”
Section: Discussionmentioning
confidence: 99%
“…They incubated rat pancreatic tumor cells (AR42J) with conventional chemotherapies (5-fluorouracil, cisplatin or doxorubicin) in the presence of melatonin and observed that this treatment caused greater mitochondrial membrane depolarization and an elevated the number of cells that underwent apoptosis relative to cells treated only with the pharmaceutical drugs. Similarly, fewer hamsters injected with N-nitrosobis (2-oxopropyl) amine (BOP) developed pancreatic cancer if they were concurrently given melatonin and those that did develop cancer survived longer [239,240]. The authors attributed the beneficial effects of melatonin to its ability to regulate the cellular redox balance.…”
Section: Melatonin and Cancer Progressionmentioning
confidence: 99%